Activity Of Ethanol Extract Namnam (Cynometra cauliflora L.) Leaves Toward Antioxidant - Anliza, Syarah; Rachmawati, Nurmeily (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2023)
One of the natural defense systems that an organism had to prevent exposure from free radicals is by forming a number of compounds that act as antioxidants. One of the substances that can prevent these free radicals are enzymes produced in the body such as glutathione peroxidase enzymes, catalase, and others. The amount of these antioxidants can be added with intake from outside the body. This antioxidant is a type of natural antioxidant that can be found in plants. Namnam plants contain phytochemical compounds such as flavonoids, tannins, phenolics, and terpenoids. These compounds can act as antioxidants. To obtain these antioxidants, the extraction process was carried out by using ethanol in a ratio of 1:5 through a maceration process for 3x24 hours. The samples used were young and old Namnam leaves each for 100 gram. The extract obtained was then tested for antioxidant activity using the DPPH method with measurements using an ELISA spectrophotometer at a wavelength of 517 nm. The positive control used was ascorbic acid. After that, the absorbance measurement results obtained will be used to measure the IC50 value. This value shows the antioxidant activity from the extract that has been made. Old Namnam leaves generate IC50 results of 9.58 ppm, while young Namnam leaves generate IC50 results of 28.93 ppm. Based on this data, the antioxidants in old Namnam leaves give a greater IC50 value than young Namnam leaves.